Mempersiapkan Lulusan SMA melalui Pelatihan Penulisan Curriculum Vitae / CV - Alienra Davry Nanda Kadun MT; Terianus Luther Safkaur (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Career mentoring will help students prepare their intellectual capacity and skills for career advancement. Students need to be guided to explore the careers they are interested so that they can achieve their full potential. Writing a Curriculum Vitae can be used as a medium for career advancement. This program takes the form of training for students of SMA Yapend 45 Entrop who will become a new workforce in the future. The purpose of this service is to provide students with CV writing skills to help them prepare for their dream careers even more as a mean for self-promotion.